Climate variability and water stress effects on oil palm (Elaies guineensis Jacq.) productivity in Malaysia - Teh, Christopher Boon Sung; Zaibon, Syaharudin; Sani, Idris; Sim, Choon Cheak (Malaysian Palm Oil Board (MPOB), 2024)
Oil palm is a key pillar of Malaysia’s socio-economic development, contributing to the nation’s economic stability, and is also a major driver of the global oil industry. However, climate variability has progressively reduced the productivity of oil palm (OP) by subjecting it to water stress through inadequate and irregular rainfall, prolonged dry spells, and elevated temperatures. This article reviews past literature and provides useful insights into the effects of climate elements and the physiological and agronomic effects of water stress on OP. Water stress impairs the physiological and metabolic functions of OP, particularly stomatal conductance, leaf water potential, proline synthesis, sex differentiation, and water use efficiency. These combined effects diminish the biomass and yield of OP. This review also highlights the temporal variability of climate and identifies the role of various soil properties related to water stress. It presents climate projections threatening OP sustainability and presents possible solutions. Additionally, the specific fraction of plantavailable water necessary for triggering water stress remains under-researched. The relationship between various physiological and genetic mechanisms that control stomatal response during water stress is unclear. The efficiencies of various irrigation approaches and water conservation measures must also be re-evaluated based on climate predictions.